2015
DOI: 10.1371/journal.pone.0110596
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effect of Yuzu and Hesperidin on Left Ventricular Remodeling and Dysfunction in Rat Permanent Left Anterior Descending Coronary Artery Occlusion Model

Abstract: Left ventricular (LV) remodeling, which includes ventricular dilatation and increased interstitial fibrosis after myocardial infarction (MI), is the critical process underlying the progression to heart failure. Therefore, a novel approach for preventing LV remodeling after MI is highly desirable. Yuzu is a citrus plant originating in East Asia, and has a number of cardioprotective properties such as hesperidin. However, no study has proved whether yuzu can prevent LV remodeling. The aim of this study was to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 34 publications
2
10
0
1
Order By: Relevance
“…S4 . These results demonstrated that yuzu peel has anti-inflammatory effect, as reported previously 12,16 .…”
Section: Anti-in Ammatory Effect Of Yuzu Peelsupporting
confidence: 90%
See 1 more Smart Citation
“…S4 . These results demonstrated that yuzu peel has anti-inflammatory effect, as reported previously 12,16 .…”
Section: Anti-in Ammatory Effect Of Yuzu Peelsupporting
confidence: 90%
“…It has been reported that yuzu contains many bioactive compounds that show anti-inflammatory and/or antioxidant activities, including ascorbic acid, β-carotene, flavonoids, and limonoids 15 . The extract of yuzu inhibits platelet aggregation, prevents myocardial infarction-induced ventricular dysfunction and structural remodeling of myocardium, and exerts an antidiabetic effect 11,16,17 . Although yuzu has many health benefits, there is no report of its beneficial effects on ulcerative colitis.…”
Section: Introductionmentioning
confidence: 99%
“…In a rat model of left ventricular remodelling, induced by a permanent left anterior descending coronary artery (LAD) occlusion, cardiac dysfunction, myocyte apoptosis and inflammation were significantly attenuated by hesperidin (30 mg/kg/day, oral gavage), via an inhibition of caspase-3 activity, myeloperoxidase expression, α-smooth muscle actin expression, and matrix metalloproteinase-2 activity. In the same study, hesperidin prevented also myocardial infarction-induced ventricular dysfunction and structural remodelling of myocardium [97]. Finally, hesperidin (100 mg/kg/day, oral gavage) proved also to exert beneficial cardioprotective activity in a cardiac I/R injury in diabetic rats when performed a LAD occlusion an effect mediated by PPAR-γ pathway [98].…”
Section: Flavanonesmentioning
confidence: 75%
“…The methanol extract of yuzu could be beneficial for individuals at high risk of cardiovascular disease because it inhibits platelet aggregation [ 159 ]. Yuzu extract could be useful in treating heart failure as it prevents myocardial infarction (MI)-induced ventricular dysfunction and structural remodeling of myocardium [ 160 ].…”
Section: Biological Propertiesmentioning
confidence: 99%